Effect of Crossing C57BL/6 and FVB Mouse Strains on Basal Cytokine Expression. (5th March 2015) - Szade, Agata; Nowak, Witold N.; Szade, Krzysztof; Gese, Anna; Czypicki, Ryszard; Waś, Halina; Dulak, Józef; Józkowicz, Alicja
Abstract : C57BL/6 is the most often used laboratory mouse strain. However, sometimes it is beneficial to cross the transgenic mice on the C57BL/6 background to the other strain, such as FVB. Although this is a common strategy, the influence of crossing these different strains on homeostatic expression of cytokines is not known. Here we have investigated the differences in the expression of selected cytokines between C57BL/6J and C57BL/6JxFVB mice in serum and skeletal muscle. We have found that only few cytokines were altered by crossing of the strains. Concentrations of IL5, IL7, LIF, MIP-2, and IP-10 were higher in serum of C57BL/6J mice than in C57BL/6JxFVB mice, whereas concentration of G-CSF was lower in C57BL/6J. In the skeletal muscle only the concentration of VEGF was higher in C57BL/6J mice than in C57BL/6JxFVB mice. Concluding, the differences in cytokine expression upon crossing C57BL/6 and FVB strain in basal conditions are not profound.